High-ionic-conductivity solid electrolyte diaphragm as well as preparation method and application thereof

Through electrospinning and in-situ polymerization technology, a solid electrolyte separator with high ionic conductivity is prepared, which solves the problem of difficult to take into account both mechanical properties, processability and high ionic conductivity, and achieves a comprehensive performance of flexibility, high strength and high conductivity, and is suitable for high-performance lithium-ion batteries.

CN119725984AActive Publication Date: 2025-03-28TIANFU JIANGXI LAB

Patent Information

Application Number
CN202411951844.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing solid electrolyte membranes are difficult to balance between mechanical properties, processability and high ionic conductivity, which limits their application in the fields of high performance and high precision.

Method used

Polyimide porous base film is prepared by electrospinning, and its pores are filled with solid electrolyte particles with high ionic conductivity, and polymerization is initiated in combination with in situ heat to form a flexible, high-strength and high ionic conductivity solid electrolyte separator.

Benefits of technology

It significantly improves the flexibility and strength of the diaphragm, meets the needs of high-precision coating and winding processes, achieves high ionic conductivity, reduces battery internal resistance, improves safety, and is easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215044660000102
    Figure BDA0005215044660000102
Patent Text Reader

Abstract

The invention discloses a high-ionic-conductivity solid electrolyte diaphragm as well as a preparation method and application thereof, and relates to the technical field of batteries. The invention relates to a preparation method of a high-ionic-conductivity solid electrolyte diaphragm, which comprises the following steps: dissolving a polyimide precursor in a solvent 1 to obtain a spinning solution, carrying out electrostatic spinning, and curing to obtain a polyimide base membrane; dispersing electrolyte particles in a solvent 2 to obtain a turbid liquid, soaking a polyimide-based membrane in the turbid liquid, and drying to obtain the polyimide-based membrane filled with the electrolyte particles; and mixing a monomer, a lithium salt, an initiator and a solvent 3 to prepare a prepolymerization solution, coating the prepolymerization solution on the polyimide base membrane filled with the electrolyte particles, and carrying out thermal polymerization treatment to obtain the solid electrolyte diaphragm. According to the invention, the problem that mechanical properties, processability and high ionic conductivity cannot be simultaneously considered is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a high ionic conductivity solid electrolyte diaphragm and a preparation method and application thereof. Background Art

[0002] With the growing global demand for efficient and safe energy storage devices, lithium-ion batteries, as the current mainstream energy storage technology, are constantly developing towards higher energy density and higher safety performance. In this development trend, all-solid-state lithium batteries are regarded as a key research direction for the next generation of energy storage systems due to their excellent thermal stability and potential high energy density characteristics. Compared with traditional liquid electrolyte systems, all-solid-state lithium batteries have significant advantages in safety and can effectively avoid battery accidents caused by safety hazards such as flammable electrolytes and leakage.

[0003] However, despite the many advantages of all-solid-state lithium batteries, the practical application of solid electrolyte materials faces many challenges. First, some inorganic solid electrolytes, such as Li 10 GeP2S 12 Sulfides such as solid electrolytes are difficult to be effectively compatible with existing battery manufacturing processes due to their brittle texture and poor processing performance. This not only increases the difficulty of production, but also limits the widespread application of solid electrolytes in battery manufacturing.

[0004] Secondly, the insufficient mechanical properties of solid electrolyte membranes are also one of the key factors restricting their development. Due to the poor flexibility of solid electrolyte membranes, it is difficult to meet the requirements of high-precision coating, tableting and other manufacturing processes, which further limits the application of solid-state lithium batteries in high-performance and high-precision fields.

[0005] In addition, the poor contact between the solid electrolyte and the electrode interface is also one of the difficulties in current research. Poor interface contact will lead to a decrease in electrochemical performance and affect the overall performance and stability of the battery.

[0006] Finally, cost is also an important factor restricting the large-scale application of solid electrolytes. The existing preparation process is complex and the cost is high, which makes solid electrolytes face great challenges in the commercialization process.

[0007] In response to the above problems, some studies have attempted to improve the performance of solid electrolyte membranes by fiber reinforcement, electrolyte particle filling or polymer modification. For example, Chinese patent application CN111234567A discloses a method of composite modified sulfide solid electrolyte. However, although this method improves the performance of solid electrolytes to a certain extent, the preparation process is still relatively complicated, and the mechanical properties still need to be improved. Although traditional polymer electrolyte membranes have good flexibility, their ionic conductivity is low, which makes it difficult to meet the high requirements of high-rate batteries for electrolyte materials.

[0008] In summary, there is an urgent need for a new type of solid electrolyte separator that can improve mechanical properties and processability while having high ionic conductivity to meet the development needs of high energy density and high safety batteries. Summary of the invention

[0009] The technical problem to be solved by the present invention is that the existing solid electrolyte membranes have the problem that mechanical properties, processability and high ionic conductivity cannot be taken into account at the same time. The purpose is to provide a high ionic conductivity solid electrolyte membrane and its preparation method and application, which solves the problem that mechanical properties, processability and high ionic conductivity cannot be taken into account at the same time.

[0010] The present invention is achieved through the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing a high ionic conductivity solid electrolyte membrane, comprising the following steps:

[0012] The amino compound and the acid anhydride compound are dissolved in solvent 1 to obtain a polyimide precursor spinning solution, and then electrospinning is performed, and then solidified to obtain a polyimide-based film;

[0013] The electrolyte particles are dispersed in solvent 2 to obtain a suspension, the polyimide-based membrane is immersed in the suspension, and then dried to obtain a polyimide-based membrane filled with electrolyte particles;

[0014] The monomer, lithium salt, initiator and solvent 3 are mixed to prepare a prepolymer solution, and the prepolymer solution is coated on a polyimide-based film filled with electrolyte particles. After thermal polymerization treatment, a solid electrolyte separator is obtained.

[0015] As a possible design, the preparation of the polyimide-based film includes the following steps:

[0016] Weighing an amino compound and an acid anhydride compound, dissolving the amino compound and the acid anhydride compound in solvent 1, and stirring to obtain a polyimide precursor spinning solution;

[0017] Electrospinning is performed under the conditions of a voltage of 10 to 20 kV, a propulsion speed of 0.3 to 1.0 mL / h, and a receiving distance of 15 to 25 cm to form a porous fiber-based membrane;

[0018] The porous fiber-based membrane is subjected to gradient heating, with a total heating temperature of 80 to 350° C., to obtain a polyimide-based membrane, wherein the gradient heating includes three stages of gradient heating:

[0019] The temperature of the first stage is 80-150°C and the time is 30 minutes to 2 hours;

[0020] The temperature of the second stage is 150-250°C and the time is 30 minutes to 2 hours;

[0021] The temperature of the third stage is 250-350°C and the time is 1-3 hours.

[0022] As a possible design, the amino compound includes one or more of diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), 4,4'-diaminodiphenyl sulfone (DDS), 3,4'-diaminodiphenyl ether (3,4'-ODA), hexamethylenediamine (HDA), ethylenediamine (EDA), 4,4'-diaminotriphenylmethane (DAM) and fluorinated diamines (such as 6FDA derivatives);

[0023] The acid anhydride compound includes one or more of pyromellitic anhydride (PMDA), dianhydride phthalic anhydride (BTDA), 6FDA (difluorinated dianhydride) and maleic anhydride (MA);

[0024] The total solid content of the polyimide precursor spinning solution is 15-25 wt.%.

[0025] As a possible design, the solvent 1 is N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc) or N-methylpyrrolidone (NMP).

[0026] As a possible design, the particle size of the electrolyte particles is 10 to 500 nm;

[0027] The electrolyte particles include Li 10 GeP2S 12 , Li 9.5 Al 0.5 GeP2S 12 、Li7P3S 11 , Li3PS4, Li6PS5Cl, Li7La3Zr2O 12 、Li4Ti5O 12 , one or more of LiAlO2, Li3PO4, LiLaTiO3, Li3N, LiSi2N3, Li6N3Br, LiAlN2, Li2SiO3, Li4SiC, Li2Ti3C2, LiFePO4, Li3BO3 and LiAlBO;

[0028] The concentration of the suspension is 10-30 mg / mL.

[0029] As a possible design, the monomers include one or more of polyethylene glycol dimethacrylate, polymethyl acrylate, polyvinyl alcohol, polyvinylidene fluoride hexafluoropropylene and polymethacrylamide;

[0030] The lithium salt includes one or more of LiTFSI, LiClO4, LiPF6, LiFSI and LiBF4;

[0031] The initiator includes one or more of benzoyl peroxide, azobisisobutyronitrile, di-tert-butyl peroxide, hydrogen peroxide and diethyldimethylnitrile;

[0032] The solvent 3 includes one or more of acetonitrile, N,N-dimethylformamide and acetone.

[0033] As a possible design, the thickness of the prepolymer solution coated on the polyimide-based film filled with electrolyte particles is 5 to 20 μm.

[0034] As a possible design, the above-mentioned thermal polymerization treatment temperature is 60-100° C. and the time is 2-6 hours.

[0035] As a possible design, the solid electrolyte membrane is further subjected to post-treatment, wherein the post-treatment includes vacuum drying and hot pressing the solid electrolyte membrane at high temperature.

[0036] As a possible design, the high temperature vacuum drying treatment is specifically carried out at 60 to 120° C. for 8 to 24 hours;

[0037] The hot pressing treatment is specifically carried out at 80-120° C. and 5-15 MPa for 10-60 min.

[0038] In a second aspect, the present invention provides a high ionic conductivity solid electrolyte membrane prepared by the above-mentioned preparation method.

[0039] In a third aspect, the present invention provides an application of a high ionic conductivity solid electrolyte membrane prepared by the above-mentioned preparation method in the preparation of lithium ion batteries.

[0040] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0041] The present invention obtains a flexible, high-strength, and high-ionic-conductivity solid electrolyte diaphragm by filling solid electrolyte particles with high ionic conductivity in the pores of a polyimide-based membrane and using an in-situ polymerized solid polymer electrolyte as a binder.

[0042] The modified diaphragm of the present invention significantly improves flexibility and strength, and can meet the requirements of high-precision coating and winding processes; thanks to the synergistic effect of inorganic particles and polymer electrolytes, the ionic conductivity of the diaphragm can reach above 10-3S / cm at room temperature; through the in-situ polymerization of the binder, the modified diaphragm is tightly bonded to the electrode interface, and the internal resistance of the battery is significantly reduced; the diaphragm has non-flammability and high thermal stability, which significantly improves the safety of the battery; the use of electrospinning and in-situ polymerization technology makes it easy to achieve large-scale production. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with Examples. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0044] Existing solid electrolyte membranes have the problem that mechanical properties, processability and high ionic conductivity cannot be taken into account at the same time. The present invention prepares a polyimide porous base membrane by electrospinning, fills high ionic conductivity solid electrolyte particles and performs functionalization by in-situ thermal polymerization, and finally obtains a solid electrolyte membrane with excellent flexibility, mechanical properties and ionic conductivity.

[0045] A method for preparing a high ionic conductivity solid electrolyte membrane comprises the following steps:

[0046] S1, dissolving an amino compound and an acid anhydride compound in solvent 1 to obtain a polyimide precursor spinning solution, performing electrostatic spinning, and then solidifying to obtain a polyimide-based film.

[0047] The polyimide-based membrane prepared by electrospinning has a three-dimensional network structure, which can facilitate the subsequent filling of particles on the one hand, and has excellent flexibility and mechanical strength on the other hand, and can meet the requirements of high-precision coating and winding processes.

[0048] In some embodiments of the present invention, the preparation of the polyimide-based film comprises the following steps:

[0049] S11, weighing an amino compound and an acid anhydride compound, dissolving the amino compound and the acid anhydride compound in solvent 1, and stirring to obtain a polyimide precursor spinning solution.

[0050] Preferably, dissolving the amino compound and the acid anhydride compound in solvent 1 is specifically as follows: dissolving the amino compound in solvent 1, in an ice water bath at -5 to 20°C, after a first stirring for 0.5 to 5 hours, adding the acid anhydride compound, and after a second stirring for 2 to 10 hours, causing an amidation reaction to occur until the reaction is complete, thereby obtaining a polyimide precursor spinning solution.

[0051] Preferably, the molar ratio of the amino compound to the acid anhydride compound is (0.9-1.1):1.

[0052] In some embodiments of the present invention, the content of the imide precursor in the spinning solution is 10-15 wt.%.

[0053] In some embodiments of the present invention, the amino compound includes one or more of diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), 4,4'-diaminodiphenyl sulfone (DDS), 3,4'-diaminodiphenyl ether (3,4'-ODA), hexamethylenediamine (HDA), ethylenediamine (EDA), 4,4'-diaminotriphenylmethane (DAM), diaminopyridine compounds, fluorinated diamines (such as 6FDA derivatives), siloxane-containing diamines, and carboxyl- or hydroxyl-containing diamines.

[0054] In some embodiments of the present invention, the above-mentioned acid anhydride compounds include one or more of pyromellitic anhydride (PMDA), dianhydride phthalic anhydride (BTDA), 6FDA (difluorinated dianhydride), biphenyltetracarboxylic anhydride (BPDA), cyclohexanetetracarboxylic anhydride (CHDA), maleic anhydride (MA), and phenylenetetracarboxylic anhydride (s-BPDA).

[0055] Preferably, the solvent 1 comprises N,N-dimethylacetamide (DMAc) or N-methylpyrrolidone (NMP).

[0056] S12, electrospinning is performed at a voltage of 10 to 20 kV, a propulsion speed of 0.3 to 1.0 mL / h, and a receiving distance of 15 to 25 cm to form a porous fiber-based membrane.

[0057] The fiber-based membrane is a three-dimensional network structure, which is beneficial to the subsequent filling process.

[0058] Preferably, the pore size of the fiber-based membrane is 0.1 to 5 μm.

[0059] S13, gradient heating the porous fiber-based membrane, with a total heating temperature of 80 to 350° C., to obtain a polyimide-based membrane, wherein the gradient heating includes three stages of gradient heating:

[0060] The temperature of the first stage is 80-150°C and the time is 30 minutes to 2 hours;

[0061] The temperature of the second stage is 150-250°C and the time is 30 minutes to 2 hours;

[0062] The temperature of the third stage is 250-350°C and the time is 1-3 hours. Gradient temperature increase can help the thermal amidation reaction to occur.

[0063] Preferably, the heating is gradient heating, and the total heating temperature is 80-350°C.

[0064] Preferably, the polyimide-based film has a thickness of 10 to 30 μm.

[0065] Preferably, the temperature is gradually increased during the curing process, the first stage (low-temperature desolvation, preliminary cyclization) temperature: 80°C to 150°C, time: 30 minutes to 2 hours; the second stage (medium-temperature dehydration cyclization) temperature: 150°C to 250°C, time: 30 minutes to 2 hours; the third stage (high-temperature complete imidization) temperature: 250°C to 350°C, time: 1 hour to 3 hours. Heating dehydrates and cyclizes the polyamic acid to form a thermally stable polyimide to reduce internal stress and improve the mechanical strength of the membrane, and finally obtain a porous polyimide-based membrane.

[0066] S2, dispersing the electrolyte particles in the solvent 2 to obtain a suspension, immersing the polyimide-based membrane in the suspension, and drying to obtain a polyimide-based membrane filled with the electrolyte particles.

[0067] In some embodiments of the present invention, the particle size of the electrolyte particles is 10 to 500 nm.

[0068] In some embodiments of the present invention, the electrolyte particles include Li 10 GeP2S 12 (LGPS), Li 9.5 Al 0.5 GeP2S 12 、Li7P3S 11 , Li3PS4, Li6PS5Cl(LPSC), Li7La3Zr2O 12 (LLZO), Li4Ti5O 12 One or more of (LTO), LiAlO2, Li3PO4, LiLaTiO3 (LLTO), Li3N, LiSi2N3, Li6N3Br, LiAlN2, Li2SiO3, Li4SiC, Li2Ti3C2, LiFePO4 (LFP), Li3BO3 and LiAlBO. The above electrolyte particles are high ion conductivity solid electrolyte particles, and the selection of the above electrolyte particles for filling can increase the ion conductivity of the diaphragm.

[0069] Preferably, after the electrolyte particles are dispersed in the solvent 2, ultrasonic treatment is performed to obtain a suspension in which the particles are uniformly dispersed.

[0070] Preferably, the solvent 2 comprises anhydrous ethanol and / or acetone.

[0071] In some embodiments of the present invention, the concentration of the suspension is 10-30 mg / mL.

[0072] The ultrasonic treatment is specifically carried out at a frequency of 40 to 60 kHz for 10 to 30 minutes.

[0073] The polyimide-based film is immersed in the suspension for 5 to 15 minutes, taken out, and then dried at 50 to 70° C. for 1 to 3 hours.

[0074] Preferably, the above soaking and removing process is repeated 2 to 5 times. This process can ensure that the particles are evenly filled.

[0075] S3, mixing the monomer, lithium salt, initiator and solvent 3 to prepare a prepolymer solution, coating the prepolymer solution on the polyimide-based film filled with electrolyte particles, and obtaining a solid electrolyte separator after thermal polymerization treatment.

[0076] By in-situ thermal polymerization, a high ionic conductivity polymer electrolyte is polymerized on the base membrane, which can make the base membrane and the electrode interface closely bonded and improve the ionic conductivity.

[0077] Preferably, the molar ratio of the above monomer to the lithium salt is 15 to 25:1.

[0078] Preferably, the amount of the initiator is 0.5 to 1.5 wt.% of the monomer mass.

[0079] In some embodiments of the present invention, the monomers include one or more of polyethylene glycol dimethacrylate (PEGDA), polymethyl acrylate (PMMA), polyvinyl alcohol (PVA), polyvinylidene fluoride hexafluoropropylene (PVDF-HFP) and polymethacrylamide (PMA).

[0080] In some embodiments of the present invention, the above-mentioned lithium salt includes one or more of LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiClO4 (lithium perchlorate), LiPF6 (lithium hexafluorophosphate), LiFSI (lithium bis(fluorosulfonyl)imide) and LiBF4 (lithium tetrafluoroborate).

[0081] In some embodiments of the present invention, the initiator includes one or more of benzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), di-tert-butyl peroxide (DTBP), hydrogen peroxide (H2O2) and diethyldimethylnitrile (DEDM).

[0082] In some embodiments of the present invention, the solvent 3 includes one or more of acetonitrile, N,N-dimethylformamide and acetone.

[0083] In some embodiments of the present invention, the thickness of the prepolymer solution applied to the polyimide-based film filled with electrolyte particles is 5 to 20 μm. If it is too thin, the mechanical strength is too low and the lithium battery cannot be processed and manufactured. If it is too thick, the impedance of the diaphragm will increase and the charging and discharging performance of the lithium battery will be reduced. Therefore, the thickness is preferably 5 to 20 μm.

[0084] In some embodiments of the present invention, the thermal polymerization treatment temperature is 60-100° C. and the time is 2-6 hours.

[0085] In some embodiments of the present invention, the solid electrolyte membrane is further subjected to post-treatment, and the post-treatment includes vacuum drying and hot pressing the solid electrolyte membrane at high temperature.

[0086] In some embodiments of the present invention, the high temperature vacuum drying treatment is specifically carried out at 60 to 120° C. for 8 to 24 hours. Under such conditions, the residual solvent and unreacted products can be removed.

[0087] In some embodiments of the present invention, the heat pressing treatment is specifically carried out at 80-120° C. and 5-15 MPa for 10-60 min. The mechanical properties and interface bonding strength of the diaphragm can be improved by heat pressing treatment under such conditions.

[0088] The present invention also provides a high ion conductivity solid electrolyte membrane prepared by the above preparation method.

[0089] The present invention also provides the use of a high ion conductivity solid electrolyte diaphragm prepared by the above preparation method in the preparation of lithium ion batteries.

[0090] Example 1

[0091] A method for preparing a high ionic conductivity solid electrolyte membrane comprises the following steps:

[0092] S1. Preparation of polyimide-based film

[0093] Preparation of polyimide precursor spinning solution: Weigh the amino compound ODA (4,4'-diaminodiphenyl ether) and the anhydride compound BPDA (biphenyltetracarboxylic anhydride) in a molar ratio of 1:1, and add the two to solvent 1 (NMP, N-methylpyrrolidone). Mechanically stir for 4 hours under ice water bath (10°C) to fully react to form a polyamic acid precursor solution with a solid content of 20wt.%. Electrospinning: The above polyimide precursor spinning solution is electrospun to form a porous fiber-based membrane under the conditions of voltage 15kV, propulsion speed 0.5mL / h, and receiving distance 20cm. The fiber pore size range is 0.5-2μm. Thermal treatment curing: The porous fiber-based membrane is subjected to gradient temperature treatment: the first stage: curing at 100°C for 1h; the second stage: curing at 200°C for 2h; the third stage: curing at 350°C for 3h. Finally, a polyimide-based membrane with a thickness of 15μm is obtained.

[0094] S2. Filling electrolyte particles

[0095] Preparation of suspension: Electrolyte particles (Li 10 GeP2S 12 , particle size 50-100nm, ionic conductivity 10-3S / cm) was dispersed in solvent 2 (anhydrous ethanol) and ultrasonically treated at a frequency of 50kHz for 20min to obtain a uniform suspension with a concentration of 20mg / mL. Filling treatment: The polyimide-based membrane was immersed in the suspension for 10min, then dried at 60℃ for 2h, and the immersion and drying were repeated 3 times to obtain a polyimide-based membrane uniformly filled with electrolyte particles.

[0096] S3. Preparation of solid electrolyte membrane

[0097] Preparation and coating of prepolymer solution: Mix monomer (PEGDA), lithium salt (LiTFSI, monomer to lithium salt molar ratio is 20:1), initiator (IBN, amount is 1wt.% of monomer mass) and solvent 3 (anhydrous acetonitrile) to prepare prepolymer solution. The prepolymer solution is evenly coated on the polyimide-based film filled with electrolyte particles with a coating thickness of 10μm. Thermal polymerization: Thermal polymerization treatment is carried out at 80°C for 4h to obtain a solid electrolyte separator.

[0098] S4. Post-processing

[0099] High temperature vacuum drying: vacuum drying the solid electrolyte membrane at 80°C for 12 hours to remove residual solvent and unreacted products. Hot pressing: hot pressing at 100°C and 10MPa for 30 minutes to improve the mechanical properties and interface bonding strength of the membrane and obtain a finished solid electrolyte membrane.

[0100] Example 2

[0101] A method for preparing a high ionic conductivity solid electrolyte membrane comprises the following steps:

[0102] S1. Preparation of polyimide-based film

[0103] Preparation of polyimide precursor spinning solution: Weigh the amino compound ODA (4,4'-diaminodiphenyl ether) and the acid anhydride compound PMDA (pyromellitic anhydride) in a molar ratio of 1:1, and add the two to solvent 1 (DMAc, N,N-dimethylacetamide). Mechanically stir for 5 hours under ice water bath (5°C) to fully react to form a polyamic acid precursor solution with a solid content of 20wt.%. Electrospinning: The above polyimide precursor spinning solution is electrospun to form a porous fiber-based membrane under the conditions of voltage 18kV, propulsion speed 0.4mL / h, and receiving distance 22cm. The fiber pore size range is 1–3μm. Thermal treatment curing: The porous fiber-based membrane is subjected to gradient temperature treatment: the first stage: curing at 80°C for 1h; the second stage: curing at 150°C for 1.5h; the third stage: curing at 350°C for 2h. Finally, a polyimide-based membrane with a thickness of 20μm is obtained.

[0104] S2. Filling electrolyte particles

[0105] Preparation of suspension: Electrolyte particles (Li7La3Zr2O 12 , particle size 100-200nm, ionic conductivity 10-3S / cm) was dispersed in solvent 2 (acetone) and ultrasonically treated at a frequency of 55kHz for 25 minutes to obtain a uniform suspension with a concentration of 15mg / mL. Filling treatment: The polyimide-based membrane was immersed in the suspension for 8 minutes, then dried at 70℃ for 3h, and the immersion and drying were repeated 4 times to obtain a polyimide-based membrane uniformly filled with electrolyte particles.

[0106] S3. Preparation of solid electrolyte membrane

[0107] Preparation and coating of prepolymer solution: Mix monomer (PVDF-HFP), lithium salt (LiPF6, monomer to lithium salt molar ratio of 15:1), initiator (BPO, amount of 0.8wt.% of monomer mass) and solvent 3 (DMAc) to prepare prepolymer solution. The prepolymer solution was evenly coated on the polyimide-based film filled with electrolyte particles with a coating thickness of 15μm. Thermal polymerization: Thermal polymerization treatment was performed at 70°C for 3h to obtain a solid electrolyte separator.

[0108] S4. Post-processing

[0109] High temperature vacuum drying: vacuum drying the solid electrolyte membrane at 100°C for 16 hours to remove residual solvent and unreacted products. Hot pressing: hot pressing at 110°C and 12MPa for 40 minutes to improve the mechanical properties and interface bonding strength of the membrane and obtain a finished solid electrolyte membrane.

[0110] Example 3

[0111] A method for preparing a high ionic conductivity solid electrolyte membrane comprises the following steps:

[0112] S1. Preparation of polyimide-based film

[0113] Preparation of polyimide precursor spinning solution: Weigh the amino compound ODA (4,4'-diaminodiphenyl ether) and the anhydride compound BPDA (biphenyltetracarboxylic anhydride) in a molar ratio of 1:1, add the two to solvent 1 (DMAc, N,N-dimethylacetamide), and perform the first mechanical stirring for 2 hours in an ice water bath (10°C). Subsequently, continue mechanical stirring for 6 hours under the same conditions to completely react to form a polyimide precursor spinning solution with a solid content of 20wt.%. Electrospinning: Under the conditions of voltage 12kV, propulsion speed 0.6mL / h, and receiving distance 18cm, the above spinning solution is electrospun to form a porous three-dimensional mesh fiber-based membrane with a fiber pore size of 1–3μm. Thermal treatment curing: The porous fiber-based membrane is subjected to gradient temperature treatment: the first stage: 80-120°C curing for 1h; the second stage: heating to 150°C curing for 2h; the third stage: heating to 350°C curing for 3h. Finally, a polyimide-based film with a thickness of 12 μm was obtained.

[0114] S2. Filling electrolyte particles

[0115] Preparation of suspension: The electrolyte particles (Li6PS5Cl, particle size 20–50 nm, ionic conductivity 10-3 S / cm) were dispersed in solvent 2 (acetonitrile) and ultrasonically treated at a frequency of 60 kHz for 30 minutes to obtain a suspension with a concentration of 25 mg / mL. Filling treatment: The polyimide-based membrane was immersed in the suspension for 12 minutes, then dried at 65 °C for 2.5 hours, and the immersion and drying were repeated 5 times to obtain a polyimide-based membrane uniformly filled with electrolyte particles.

[0116] S3. Preparation of solid electrolyte membrane

[0117] Preparation and coating of prepolymer solution: Mix monomer (PVA), polymethacrylamide (PMA), lithium salt (LiFSI, the molar ratio of monomer to lithium salt is 20:1), initiator (DTBP, the amount of initiator is 1wt.% of the monomer mass) and solvent 3 (anhydrous acetone) to prepare a prepolymer solution. The prepolymer solution is evenly coated on the polyimide-based film filled with electrolyte particles, and the coating thickness is 12μm. Thermal polymerization: Thermal polymerization treatment is carried out at 75°C for 3 hours to obtain a solid electrolyte separator.

[0118] S4. Post-processing

[0119] High temperature vacuum drying: The solid electrolyte membrane is dried at 70°C in a vacuum oven for 10 hours to remove residual solvent and unreacted products.

[0120] Hot pressing treatment: The dried solid electrolyte membrane is hot pressed at 90°C and 8MPa for 20 minutes to further improve the mechanical properties and interface bonding strength of the membrane, and finally obtain a finished solid electrolyte membrane.

[0121] Comparative Example 1

[0122] This comparative example is basically the same as Example 1, except that step S2 is omitted.

[0123] Comparative Example 2

[0124] This comparative example is basically the same as Example 1, except that step S3 is omitted.

[0125] Comparative Example 3

[0126] This comparative example is basically the same as Example 1, except that step S4 is omitted.

[0127] Comparative Example 4

[0128] This comparative example is basically the same as Example 1, except that step S4 does not perform hot pressing.

[0129] Experimental example

[0130] The samples of Examples 1 to 3 and Comparative Examples 1 to 4 were respectively combined with PP separators and PE separators to conduct ion conductivity in electrolyte.

[0131] The ionic conductivity test method is as follows:

[0132] The ionic conductivity test procedure of the diaphragm usually includes the following steps:

[0133] 1. Pretreatment of diaphragm

[0134] Cut the PP or PE diaphragm into a size suitable for testing (usually small pieces with a diameter of 10 to 20 mm).

[0135] Clean the membrane surface with deionized water and anhydrous ethanol to remove possible surface impurities.

[0136] The diaphragm is dried in a vacuum drying oven, the temperature is generally set at 60°C, and the time is 4 to 6 hours to remove the moisture or solvent adsorbed on the surface.

[0137] 2. Impregnation of electrolyte

[0138] Prepare a suitable electrolyte (such as a lithium salt solution, for example 1M LiPF6 dissolved in EC / DMC solvent).

[0139] Completely immerse the diaphragm in the electrolyte for 12 to 24 hours to ensure that the inside of the diaphragm is fully soaked.

[0140] 3. Assembling the test battery

[0141] A stainless steel-stainless steel symmetrical structure (SS|diaphragm|SS) was used as the test cell.

[0142] In the battery fixture, the separator soaked in electrolyte is sandwiched between two stainless steel electrodes.

[0143] Make sure that the electrode and diaphragm are in good contact in the fixture without leaks or diaphragm wrinkles.

[0144] 4. Test environment preparation

[0145] The test unit was placed in a thermostat to control the temperature (eg, 25° C.).

[0146] Let it stand for a while (usually 30 minutes to 1 hour) to ensure that the electrolyte and separator are stable.

[0147] 5. Test instrument and parameter setting

[0148] The measurements were performed using an electrochemical impedance spectroscopy (EIS) tester.

[0149] Frequency range: Typically 1MHz to 1Hz.

[0150] AC amplitude: 5~10mV.

[0151] 6. Data collection and calculation

[0152] Measure the resistance (R) and obtain the impedance value of the diaphragm through the real axis intercept at the high frequency end of the Nyquist plot.

[0153] Calculate the ionic conductivity according to the formula:

[0154] σ: ionic conductivity (S / cm)

[0155] L: Thickness of diaphragm (cm)

[0156] R: Measured resistance value (Ω)

[0157] A: effective area of ​​diaphragm (cm 2 ).

[0158] 7. Data Analysis

[0159] Analyze ionic conductivity based on test results and compare the performance of different membranes.

[0160] Through the above steps, the ionic conductivity of PP and PE separators can be accurately determined, providing a basis for the evaluation of their electrochemical properties.

[0161] The results are shown in Table 1.

[0162] Table 1

[0163]

[0164] Combined with Table 1, it can be inferred that the ionic conductivity of the comparative sample will be significantly reduced due to the omission of key steps.

[0165] Comparing Example 1 with Comparative Example 1, Comparative Example 1 omits step S2 compared to Example 1. The main function of step S2 is to fill the polyimide-based membrane with electrolyte particles with high conductivity. This step plays a core role in improving ionic conductivity. If this step is omitted, the polyimide-based membrane will lack electrolyte particles, the ion conduction path will be blocked, and the conductivity will be significantly reduced.

[0166] Comparing Example 1 and Comparative Example 2, Comparative Example 1 omits step S3 compared to Example 1. The function of step S3 is to form a continuous solid electrolyte layer by coating the prepolymer solution and thermal polymerization, thereby further optimizing the ion conduction path. If this step is omitted, the surface of the electrolyte membrane lacks an effective ion-conducting layer structure, and the ion conductivity will be significantly reduced.

[0167] Comparing Example 1 and Comparative Example 3, Comparative Example 1 omits step S4 compared to Example 1. The high-temperature vacuum drying and hot pressing treatment in step S4 mainly improve the mechanical properties and interface bonding strength of the diaphragm, and indirectly affect the conductivity. If this step is omitted, the interface performance of the diaphragm is poor, which may affect the stability of some ion conduction paths, but the impact is relatively small.

[0168] Comparing Example 1 and Comparative Example 3, Comparative Example 1 does not perform hot pressing treatment in step S4 compared to Example 1. Hot pressing treatment improves the interface bonding strength and mechanical properties of the diaphragm, and plays an auxiliary role in the stability of the ion conduction path. If hot pressing treatment is not performed, the conductivity may decrease slightly, but it is still close to the level of the embodiment.

[0169] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a high ionic conductivity solid electrolyte membrane, characterized in that: The steps include: The amino compound and the acid anhydride compound are dissolved in solvent 1 to obtain a polyimide precursor spinning solution, and then electrospinning is performed, and then solidified to obtain a polyimide-based film; The electrolyte particles are dispersed in solvent 2 to obtain a suspension, the polyimide-based membrane is immersed in the suspension, and then dried to obtain a polyimide-based membrane filled with electrolyte particles; The monomer, lithium salt, initiator and solvent 3 are mixed to prepare a prepolymer solution, and the prepolymer solution is coated on a polyimide-based film filled with electrolyte particles. After thermal polymerization treatment, a solid electrolyte separator is obtained.

2. The method for preparing a high ionic conductivity solid electrolyte membrane according to claim 1, characterized in that: The preparation of the polyimide-based film comprises the following steps: Weighing an amino compound and an acid anhydride compound, dissolving the amino compound and the acid anhydride compound in solvent 1, and stirring to obtain a polyimide precursor spinning solution; Electrospinning is performed under the conditions of a voltage of 10 to 20 kV, a propulsion speed of 0.3 to 1.0 mL / h, and a receiving distance of 15 to 25 cm to form a porous fiber-based membrane; The porous fiber-based membrane is subjected to gradient heating, with a total heating temperature of 80 to 350° C., to obtain a polyimide-based membrane, wherein the gradient heating includes three stages of gradient heating: The temperature of the first stage is 80-150°C and the time is 30 minutes to 2 hours; The temperature of the second stage is 150-250°C and the time is 30 minutes to 2 hours; The temperature of the third stage is 250-350°C and the time is 1-3 hours.

3. The method for preparing a high ionic conductivity solid electrolyte membrane according to claim 1, characterized in that: The amino compound includes one or more of diaminodiphenyl ether, p-phenylenediamine, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl ether, hexamethylenediamine, ethylenediamine, 4,4'-diaminotriphenylmethane and fluorinated diamine; The acid anhydride compound includes one or more of pyromellitic anhydride, dianhydride phthalic anhydride, 6FDA and maleic anhydride; The total solid content of the polyimide precursor spinning solution is 15-25 wt.%.

4. The method for preparing a high ionic conductivity solid electrolyte membrane according to claim 1, characterized in that: The solvent 1 is N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone.

5. The method for preparing a high ionic conductivity solid electrolyte membrane according to claim 1, characterized in that: The electrolyte particles have a particle size of 10 to 500 nm; The electrolyte particles include Li 10 GeP2S 12 , Li 9.5 Al 0.5 GeP2S 12 、Li7P3S 11 , Li3PS4, Li6PS5Cl, Li7La3Zr2O 12 、Li4Ti5O 12 , one or more of LiAlO2, Li3PO4, LiLaTiO3, Li3N, LiSi2N3, Li6N3Br, LiAlN2, Li2SiO3, Li4SiC, Li2Ti3C2, LiFePO4, Li3BO3 and LiAlBO; The concentration of the suspension is 10-30 mg / mL.

6. The method for preparing a high ionic conductivity solid electrolyte membrane according to claim 1, characterized in that: The monomers include one or more of polyethylene glycol dimethacrylate, polymethyl acrylate, polyvinyl alcohol, polyvinylidene fluoride hexafluoropropylene and polymethacrylamide; The lithium salt includes one or more of LiTFSI, LiClO4, LiPF6, LiFSI and LiBF4; The initiator includes one or more of benzoyl peroxide, azobisisobutyronitrile, di-tert-butyl peroxide, hydrogen peroxide and diethyldimethylnitrile; The solvent 3 includes one or more of acetonitrile, N,N-dimethylformamide and acetone.

7. The method for preparing a high ionic conductivity solid electrolyte membrane according to claim 1, characterized in that: The thickness of the prepolymer solution coated on the polyimide-based film filled with electrolyte particles is 5 to 20 μm.

8. The method for preparing a high ionic conductivity solid electrolyte membrane according to claim 1, characterized in that: The thermal polymerization treatment temperature is 60-100° C. and the time is 2-6 hours.

9. The method for preparing a high ionic conductivity solid electrolyte membrane according to claim 1, characterized in that: The solid electrolyte membrane is further subjected to post-treatment, which includes vacuum drying and hot pressing the solid electrolyte membrane at high temperature.

10. The method for preparing a high ionic conductivity solid electrolyte membrane according to claim 9, characterized in that: The high temperature vacuum drying treatment is specifically carried out at 60-120° C. for 8-24 hours; The hot pressing treatment is specifically carried out at 80-120° C. and 5-15 MPa for 10-60 min.

11. A high ionic conductivity solid electrolyte membrane, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 10.

12. Use of a high ionic conductivity solid electrolyte membrane prepared by the preparation method according to any one of claims 1 to 10 in the preparation of lithium ion batteries.

Citation Information

Patent Citations

  • Inorganic coating process for preparing high-weather-resistance titanium dioxide

    CN111234567A

  • Novel solid electrolyte and preparation method thereof

    CN109286038A

  • In-situ thermocuring nanofiber composite solid electrolyte as well as preparation method and application thereof

    CN115763966A

  • Preparation method of polyimide-based composite diaphragm for lithium battery

    CN118783028A

Cited By

  • A solid-state battery and its composite electrolyte, preparation and application

    CN120357039B

  • A method for soap-free emulsion polymerization for diaphragm mixed coating

    CN122502963A